Ethical awareness and practice of accountants in Iloilo City - Bedoña, Peterose; Cagampang, Kay.; Origen, Michelle; Valenzuela, Rayanne (2007.)
The general objective of the study is to measure the ethical awareness and practice among accountants in Iloilo City. Specifically, this study intends to: 1) Determine the level of ethical awareness among accountants in Iloilo City; 2) Determine the level of ethical practice among accountant in Iloilo City; and 3)Propose actions to be taken to promote ethical awareness among students. In determining the sample of the study, a list of Certified Public Accountants (PICPA) - Iloilo Chapter. The sample scheme for this study employed purposive sampling design by selecting CPA's in PICPA who are active for at least five years. Then the sample will include at least 50% plus one from the provided list. Descriptive and quantitative analysis of data generated was made through the computer. assised Statistical Package for Social Sciences (SPSS). Data and info from the survey form were coded for proper identification and categorization. These categorized responses were organized and presented as appropriated tables. Responses to probe question that are qualitative in nature were translated into categories to facilitate analysis and reporting. Accountants in Iloilo City are aware of business ethics. They also said that the accounting profession is likewise aware. They are also aware about unethical practices and even said that these exit within their company. They Knew about their existence because they witnessed it done by others. The accountants practice ethics most of the time and also pointed out that the Accounting profession likewise practice ethics most of the time. Fortunately their company practices business ethics as well as sanctions against unethical behaviors which complement the respondents' aim to eliminate unethical practices. However, they also pointed out that their companies sometimes become unethical or ethical. But they rated their companies effective in the efforts to eliminate the unethical practices. Accountants defines ethical as the customary behavior in society but they practice ethics according to what their feelings tell them. The best source of knowledge on business ethics, as identified by the respondents, are the books, journals, magazines, newspapers and other reading materials but the one with the greatest influence are the training, conferences and symposiums. though it is the teacher that provides the idea on what business ethics is, it is the mother who has the greatest influence in shaping and strengthening a person's application of ethics. The respondents are in favor of the sanctions in order to minimize the unethical practices and this likewise is the reason of the company for implementing the sanctions. Dismissal for unethical business behavior is the most preferred type of sanction by the respondents. Respondents identified reprimands as the frequently practiced sanction by their company. Most of the respondents want to eliminate unethical practices for aa better country. Their company eliminates unethical practice also for a better country as well as for fair progress among stakeholders. Fraudulent statements together with bribery are the most popular unethical practices that the respondents are aware of and these are also the unethical practices that are usually practiced within the company, as pointed out by respondents. The respondents claimed that sexual harassment, kiting, and lapping have already been addressed by their companies and do not exist in their offices. Bribery if the unethical practice that is most likely to be eliminated by the respondents first followed by fraudulent statements and so on. Respondents specified effective internal control as the best action to eliminate unethical practices. However, the action mostly used by their company to eliminate, if not reduce, unethical behaviors is lifestyle check/background investigation. In conclusion, the accountants in Iloilo city are ethically aware at an average level and that ethics is practiced highly. The researchers recommend that the schools and other educational institutions stress the importance of business ethics in their students' life as well as in their professional life. If possible and feasible, business ethics should be given as a separate subject. Since trainings, conferences and symposiums are very influential, students should be encouraged to attend these should it be available at school or the school itself can offer it. companies should continue on implementing sanctions against unethical practices. Further, trainings and seminars/talks could help veteran professionals be reminded of the business ethics.
[Research Paper] (BA 199-Business Research) -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 2007.